CLASSROOM OBSERVATIONS: TECHNOLOGY-BASED TEACHING PRACTICES - Laylo Turdiboyeva; Eshdavlatova Adiba Zafarovna (TADQIQOTLAR, 2026)
Abstract This study examines technology-based teaching through classroom observations, highlighting how digital tools enhance engagement, interaction, and participation. It finds that multimedia, online platforms, and assessments support learner-centered environments and motivation. Effective integration depends on teachers’ skills and alignment with objectives, improving instructional quality and creating more meaningful, responsive learning experiences.